A 37‐year prospective study of neuroticism and extraversion in women followed from mid‐life to late life. (19th February 2013) - Billstedt, E.; Skoog, I.; Duberstein, P.; Marlow, T.; Hällström, T.; André, M.; Lissner, L.; Björkelund, C.; Östling, S.; Waern, M.
<x xml:space="preserve">Abstract</x> Objective Personality traits are presumed to endure over time, but the literature regarding older age is sparse. Furthermore, interpretation may be hampered by the presence of dementia‐related personality changes. The aim was to study stability in neuroticism and extraversion in a population sample of women who were followed from mid‐life to late life. Method A population‐based sample of women born in 1918, 1922 or 1930 was examined with the Eysenck Personality Inventory (EPI) in 1968–1969. EPI was assessed after 37 years in 2005–2006 (n = 153). Data from an interim examination after 24 years were analysed for the subsample born in 1918 and 1922 (n = 75). Women who developed dementia at follow‐up examinations were excluded from the analyses. Results Mean levels of neuroticism and extraversion were stable at both follow‐ups. Rank‐order and linear correlations between baseline and 37‐year follow‐up were moderate ranging between 0.49 and 0.69. Individual changes were observed, and only 25% of the variance in personality traits in 2005–2006 could be explained by traits in 1968–1969. Conclusion Personality is stable at the population level, but there is significant individual variability. These changes could not be attributed to dementia. Research is needed to examine determinants of these changes, as well as their clinical implications.